Athlete profiles along grit, sport orientation and sport persistence based on a quantitative research on Hungarian athletes - Karolina Eszter Kovács (Frontiers in Sports and Active Living)
IntroductionSport persistence, the sustained engagement in sporting activities, is influenced by a combination of intrinsic and extrinsic motivational factors. Understanding these factors is crucial for supporting long-term athlete commitment and preventing dropout. The study examines athlete profiles based on sport persistence, sport orientation, and grit, aiming to identify distinct clusters that reveal different psychological and sociodemographic characteristics.MethodsA survey was conducted among 1,105 young athletes (aged 14–25) from secondary and tertiary education institutions in Hungary. The sample included both competitive and recreational athletes. Data collection involved validated psychological measures, including the Sport Persistence Questionnaire, Short Grit Scale, Sport Orientation Questionnaire, beside a block of sociodemographic questions. Cluster analysis (K-Means clustering) was used to identify athlete profiles based on sport persistence, grit, and sport orientation.ResultsFour distinct athlete profiles emerged: (1) Consistently persistent athletes (n = 363; high levels of sport persistence, grit, and sport orientation); (2) Athletes prone to dropout (n = 174; low level persistence, grit, and sport orientation); (3) Oriented lagging athletes (n = 387; moderate sport orientation but lower grit and persistence); (4) Disoriented persistent athletes (n = 180; high grit but low sport orientation). Sociodemographic factors, such as parental employment status and educational background, significantly influenced group membership.DiscussionThese results indicate that gender, educational level, parental employment, and sport type significantly influence an athlete's likelihood of maintaining sport participation. The findings also suggest that competitive team sports support networks may contribute to sustained engagement, while university transitions and socioeconomic challenges can lead to a decline in sport persistence.